Single and combination effects of dietary aflatoxin and adsorbents (palyvinylpolypyrrolidone and benionite) on some performance parameters of broiler chickens - Halis Oğuz; Ömer Demet (Eurasian Journal of Veterinary Sciences)
This study was concluded 10 determine the elfects o1 aflatoxin on some the performance parameters of broiler chicks and also to evaluate the preventive efficacy o1 various adsorbents jpolyviniylpolypyrrolidone; PVPP and benionite; BNT). given as teed additives, on expenmenlalty induced atlatoxicosis. A total ol 147 day-old unvaccinated broiler chicks (Avian) were divided into seven groups (control, AF, PVPP, AF+PVPP, PVPP+BNT, AF+PVPP+BNT, and AF+BNT) each consist of 21 chickens. 2.5 mg ol AF (total allatoxin; 83.1% 8,, 13.0% B2, 2,8% G1 and 1,1% G2),